The Problem of Fair Management in Politics: Religious Argument and Personal Interest Argument - Gokhan Mitroglou (GoAcademica Research & Publishing, 2020)
This study analyzes politics tradition in Sunn political thought in terms of exploring the problem of just ruling. In the relevant literature, the dominant approach considers Siyāsatnāmas as ethical advice in general and regards them as ineffective against an un-just ruler who has no ethical concern. This study criticizes this dominant view by claiming that in addition to the religious / ethical argument to promote a just rule, the Siyāsatnāma tradition develops a second argument designed specifically for an unjust ruler who ignores ethi-cal advice. This second argument is ignored by the dominant position about the Siyāsatnāma tradition. I have called it self-interest argument in this study. An unjust ruler's self interest is to maintain, empower, and hand down his power to his descendants. The self-interest argument tries to convince a ruler who dismisses ethical advice to adopt just ruling by revealing that even for an unjust ruler the best strategy is just ruling to reach for his worldly aims.